Life in Ancient Egypt - Adolf Erman 1854-1937; H. M. Tirard; Jon Manchip White (USA Dover Publications, 1971)
A classical history of social, political, cultural, and religious developments among the ancient Egyptians.
ch. 1. The land of Egypt -- ch. 2. The people of Egypt -- ch. 3. History of ancient Egypt -- ch. 4. The king and his court -- ch. 5. Political conditions in Egypt under the old empire -- ch. 6. Political conditions in Egypt under the new empire -- ch. 7. The police and the courts of justice -- ch. 8. Family life -- ch. 9. The house -- ch. 10. Dress -- ch. 11. Recreation -- 12. Religion -- ch. 13. The dead -- ch. 14. Learning -- ch. 15. Literature -- 16. The plastic arts -- ch. 17. Agriculture -- ch. 18. Arts and crafts -- ch. 19. Traffic and trade -- ch. 20. War.
Translation of Aegypten und aegyptisches Leben im Altertum.
Reprint of the 1894 ed.
Keywords: History, Geography and Archaeology (3GdJGQjN hGdLZQGajG hGdBKGQs; General; Ancient Egypt